Finding binaries from phase modulation of pulsating stars with Kepler – VI. Orbits for 10 new binaries with mischaracterized primaries. Issue 4 (27th February 2020) - Murphy, Simon J; Barbara, Nicholas H; Hey, Daniel; Bedding, Timothy R; Fulcher, Ben D
ABSTRACT: Measuring phase modulation in pulsating stars has proven to be a highly successful way of finding binary systems. The class of pulsating main-sequence A and F variables, known as δ Scuti stars consists of particularly good targets for this, and the Kepler sample of these has been almost fully exploited. However, some Kepler δ Scuti stars have incorrect temperatures in stellar properties catalogues, and were missed in previous analyses. We used an automated pulsation classification algorithm to find 93 new δ Scuti pulsators among tens of thousands of F-type stars, which we then searched for phase modulation attributable to binarity. We discovered 10 new binary systems and calculated their orbital parameters, which we compared with those of binaries previously discovered in the same way. The results suggest that some of the new companions may be white dwarfs.